Response and recovery mechanisms of river microorganisms to gradient concentrations of estrogen - Qin, Dan; Li, Yan; Chen, Nengwang; Hu, Anyi; Yu, Chang-Ping (Frontiers in Microbiology, 2023)
As an important ecological system on the earth, rivers have been influenced by the rapid development of urbanization, industrialization, and anthropogenic activities. Increasingly more emerging contaminants, such as estrogens, are discharged into the river environment. In this study, we conducted river water microcosmic experiments to investigate the response mechanisms of in-situ microbial community when exposed to different concentrations of target estrogen (estrone, E1). The results showed that both exposure time and concentrations shaped the diversity of microbial community when exposed to E1. Deterministic process played a vital role in influencing microbial community over the entire sampling period. The influence of E1 on microbial community could last for a longer time even after the E1 has been degraded. The microbial community structure could not be restored to the undisturbed state by E1, even if disturbed by low concentrations of E1(1 μg/L and 10 μg/L) for a short time. Our study suggests that estrogens could cause long-term disturbance to the microbial community of river water ecosystem and provides a theoretical basis for assessing the environmental risk of estrogens in rivers.